2020
DOI: 10.3390/cells9071581
|View full text |Cite
|
Sign up to set email alerts
|

MHC Class I-Restricted TCR-Transgenic CD4+ T Cells Against STEAP1 Mediate Local Tumor Control of Ewing Sarcoma In Vivo

Abstract: In this study we report the functional comparison of T cell receptor (TCR)-engineered major histocompatibility complex (MHC) class I-restricted CD4+ versus CD8+ T cells targeting a peptide from six transmembrane epithelial antigen of the prostate 1 (STEAP1) in the context of HLA-A*02:01. STEAP1 is a tumor-associated antigen, which is overexpressed in many cancers, including Ewing sarcoma (EwS). Based on previous observations, we postulated strong antitumor potential of tumor-redirected CD4+ T cells tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Cytokines and chemokines in conditioned medium from cell cultures were analyzed using the Bio-Plex Pro Human Chemokine TNF-α Set (171BK55MR2) and Bio-Plex Human Cytokine Screening Panel, 48-plex panel (both Bio-Rad, Munich, Germany) as described previously [34]. Conditioned medium was collected, centrifuged at 2000× g for 10 min at 4 • C, and stored at −80 • C until further analysis.…”
Section: Cytokine Single-and Multiplex Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokines and chemokines in conditioned medium from cell cultures were analyzed using the Bio-Plex Pro Human Chemokine TNF-α Set (171BK55MR2) and Bio-Plex Human Cytokine Screening Panel, 48-plex panel (both Bio-Rad, Munich, Germany) as described previously [34]. Conditioned medium was collected, centrifuged at 2000× g for 10 min at 4 • C, and stored at −80 • C until further analysis.…”
Section: Cytokine Single-and Multiplex Assaymentioning
confidence: 99%
“…Phenotypes of myeloid and T cells were assessed by flow cytometry as previously reported [30,34]. Briefly, CD14 + and CD33 + moDCs were stained with anti-CD14 (REA599), CD33 (REA775), CD80 (REA661), CD83 (REA714), CD86 (REA968), HLA-DR (REA805) and respective isotype (IT) antibodies.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Indeed, several studies with monoclonal antibodies attached to radioisotopes have demonstrated promising results in targeting and monitoring STEAP1 expression and in controlling PCa progression [ 11 , 12 ]. Likewise, several in vitro and in vivo studies revealed that STEAP1-derived peptides are immunogenic and hence suitable for recognition by cytotoxic T lymphocytes [ 13 , 14 ], suggesting their potential use in the development of anti-cancer vaccines. Altogether, these features highlight the usefulness of STEAP1 as a promising tool, either as a biomarker or as a target for anti-cancer therapies [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…These structural features highlight the usefulness of STEAP1 as a promising therapeutic target and biomarker for cancer and encouraged the development of strategies targeting STEAP1. In vitro and in vivo studies revealed mobilized dendritic cells and immunogenic STEAP1-derived peptides suitable for recognition by cytotoxic T lymphocytes for further development of anti-cancer vaccines (23). Humanized variant of anti-STEAP1 monoclonal antibody (mAb 120.545) is currently used in prostate cancer clinical trials as an antibody-drug conjugate (DSTP3086S) (24), and as a radiolabeled antibody (89Zr-DFO-MSTP2109A) for PET imaging (24,25).…”
Section: Steap1mentioning
confidence: 99%